Stroke Care During the First and the Second Waves of the COVID-19 Pandemic in a Community Hospital - Sobolewski, Piotr; Szczuchniak, Wiktor; Grzesiak-Witek, Danuta; Wilczyński, Jacek; Paciura, Karol; Antecki, Mateusz; Frańczak-Prochowski, Tadeusz; Kos, Marek; Kozera, Grzegorz (Frontiers in Neurology, 2021)
Objective: The COVID-19 infection may alter a stroke course, thus we compared stroke course during subsequent pandemic waves in stroke unit (SU) from the hospital located in the rural area. Methods: A retrospective study included all patients consecutively admitted to SU between 15 March - 31 May 2020 (“first wave”) and between 15 September - 30 November 2020 (“second wave”). We compared demographic and clinical data, treatments and outcomes of patients between the first and the second wave of pandemic and between subject with and without COVID-19 . Results: During the “first wave” 1.4% of 71 patients hospitalized due to stroke / TIA and 41.8% of 91 during the “second wave” were infected with SARS-CoV-2 (p<0.001). During the “second wave” more SU staff members were infected with COVID-19 than during the “first wave” (45.6% vs. 8.7%, p<0.001). Nevertheless, more patients underwent intravenous thrombolysis (26.4% vs. 9.9%, p<0.008) and endovascular thrombectomy (5.3% vs. 0.0%, p<0.001) during the second than the first wave. Large vessel occlusion (LVO) (OR-6.46; 95%CI 1.25-33.41; p=0.026) and higher thirty-day mortality (OR-7,73; 95%CI 1.09-54.57; p=0.04) were associated with patients infected with COVID-19. No differences regarding hemorrhagic etiology or TIAs between both waves or subgroups with and without COVID-19 existed. Conclusion: Despite the greater COVID-19 infection rate among both, SU patients, and staff during the “second wave” of the pandemic, a higher percentage of reperfusion procedures has been performed then. COVID-19 infection was associated with a higher rate of the LVO and thirty-day mortality.